2020
DOI: 10.3390/en13040878
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Exergy and Economic Analyses of a Combined Heating and Power System with Turbine-Driving Fans and Pumps in Northeast China

Abstract: The combined heating and power (CHP) system with turbine-driving fans and pumps is more efficient and economical in meeting heat demand in cold areas, however, there are no detailed studies that investigate its thermodynamic performance, improvement possibilities and economy. In this paper, the energy, exergy and economic analysis of a CHP system with turbine-driving fans and pumps operated in Northeast China were conducted to provide insights into improvement options. It is revealed that the boiler is the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
4
6
0
Order By: Relevance
“…The analysis shows that with the increase in temperature and pressure of the superheated steam (from the boiler), the steam flowrate requirement is decreased. This case-study is also in agreement with the research conducted by various researchers [27,29,30].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The analysis shows that with the increase in temperature and pressure of the superheated steam (from the boiler), the steam flowrate requirement is decreased. This case-study is also in agreement with the research conducted by various researchers [27,29,30].…”
Section: Resultssupporting
confidence: 91%
“…The comparatively reduced amount of carbon is un-combusted, decrease in ash/residue production rate which helps in improved % exergy efficiency of the boiler. This case-study is also in agreement with the research conducted by various researchers [20,[27][28][29][30]. The analysis shows that with the increase in temperature and pressure of the superheated steam (from the boiler), the steam flowrate requirement is decreased.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“… Boyaghchi and Molaie, 2015 Combined cycle 420 The sensitivity of the various components of exergy loss was studied in a practical combined cycle power plant. Li et al, 2020 Combined cycle 1989 In cold climes, a CHPP system with turbine-driven fans and pumps is more efficient and effective in providing heat demand. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Calise et al [10] have provided an overview of recent progress in assessing sustainable energy systems. Li et al [11] have analysed the economic and energy efficiency of CHP (cogeneration heat and power) systems with turbine-driven fans and pumps. Liu et al [7] have developed a mathematics and results have shown that a CO 2 heat pump system is economically and ecologically feasible, especially in areas not rich in natural gas.…”
Section: Introductionmentioning
confidence: 99%